PENGARUH FENOMENA REAL MONEY TRADE TERHADAP KEPUTUSAN PEMBELIAN DAN IMPLIKASINYA TERHADAP KEPUASAN PELANGGAN VIRTUAL ITEM COUNTER-STRIKE: GLOBAL OFFENSIVE TAHUN 2021 - Dhiyaa Arkaan; Kosasih Kosasih (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to examine and analyze the Effect of Real Money Trade Phenomenon on Purchase Decisions and Its Implications on Customer Satisfaction Virtual Item Counter-Strike: Global Offensive in 2020. This research was conducted using descriptive and verification methods, namely: collecting, presenting, analyzing and perform hypothesis testing, and make conclusions and suggestions. Samples were collected using the Hairs in Ferdinand method and the Non probability sampling technique and then resulted in a sample of 150 respondents. The analytical technique used is Likert scale analysis technique and path analysis with the tools of Method Of Successive Interval (MSI), Microsoft Office, and SPSS version 18.0. Based on the results of the analysis that has been carried out this research proves that the Real Money Trade phenomenon shows an average value of 604.4 with the criteria agree, Purchase Decision shows an average value of 575.1 with the criteria agree, and Customer Satisfaction shows an average value of 546, 8 with agreed criteria. The partial effect of Real Money Trade Phenomenon on Purchase Decisions is 72.2%, Purchase Decisions on Customer Satisfaction is 56.5%, Real Money Trade Phenomenon on Customer Satisfaction is 76.9%, it can be stated that Real Money Phenomenon provides more contribution to customer satisfaction compared to other variables.